CLASDN- An Extension in Networking for Efficient Multimedia Data Transmission - Vasundra, S; Venkatesh, D (International Journal of Computer Sciences and Engineering, 2025)
Network communication has been experiencing major changes over the last few decades as the number of Internet applications is increasing at an exponential rate. The devices that are used to access the internet, the applications that are accessed over the internet and the types of networks are changing continuously. Although layering is based on sound engineering principles and was a huge success in wired networks, the layered stack of protocols is not tuned to handle multimedia applications in interactive environment and to address this cross-layer conception is envisioned. Cross-layer collaborations can work between an existing stack of protocols and are a promising solution. To exploit adaptability crosslayering allows sharing across protocols and layers and allows information exchange. In this paper, we proposed a working technique called Cross-Layer Approach-based Software Defined Networking (CLASDN) technique that makes the multimedia delivery effectually in networks